The relationship between peer support and sleep quality among Chinese college students: the mediating role of physical exercise atmosphere and the moderating effect of eHealth literacy - Li, Jin (Frontiers in Psychology, 2024)
Background: Poor sleep quality has emerged as a prevalent health issue among college students. This study aims to explore the mechanism of sleep quality among college students by constructing a moderated mediation model. Methods: The Peer Support Scale, Physical Exercise Atmosphere Scale, eHealth Literacy Scale and Pittsburgh Sleep Quality Index were used to conduct a survey and analysis on 1,085 questionnaires, which were distributed among students from four universities in the northwest, northeast and central regions of China. Results: (1) A significant pairwise correlation exists between peer support, physical exercise atmosphere, eHealth literacy and sleep quality (P＜0.001); (2) Physical exercise atmosphere plays a mediating role between peer support and sleep quality, with a mediating effect accounting for 28.08%; (3) eHealth literacy can significantly moderate the strength of the relationships between peer support and exercise atmosphere, between peer support and sleep quality, and between physical exercise atmosphere and sleep quality. This study revealed the relationship between peer support and sleep quality among college students and its influencing mechanism, and provided theoretical and practical basis for improving college students' sleep quality from the perspectives of peer support, physical exercise atmosphere, and eHealth literacy.